Pengelolan Objek Wisata Dalam Upaya Meningkatkan Kesejahteraan Masyarakat Desa Molotabu Kecamatan Kabila Bone Kabupaten Bone Bolango - Sulila, Ismet; Nani, Yacob Noho; A, Anwar (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
Tourist Attraction Management is an activity that aims to manage, empower and utilize the potential of natural resources, especially Molotabu Beach tourism in Molotabu Village, to create a superior tourist destination area and attract tourists so that people have the opportunity to improve their standard of living through businesses around tourism. This research aims to determine the management of the Molotabu Beach tourist attraction in an effort to improve the welfare of the Molotabu Village community and to find out the factors that determine the success of managing the Molotabu Beach tourist attraction. The research method used is qualitative, namely a form of research that aims to provide a general description of various field data collected objectively with a phenomenological type. The data collection techniques used were observation, interviews with a number of informants and documentation of data analysis used using an interactive analysis model. The research results show that the management of the Molotabu Beach tourist attraction in an effort to improve the welfare of the people of Molotabu Village is quite successful but not yet fully optimal, because there are several things that still need to be addressed. This can be seen from the aspects of (1) Planning, (2) Organizing, (3) Mobilizing, (4) Supervising. Factors that determine the success of managing the Molotabu Beach tourist attraction (a) Human Resources (b) Financial Resources/Funds. These two factors still have obstacles in terms of implementation so that in the future they still need improvement.